Release profiles and morphological characterization by atomic force microscopy and photon correlation spectroscopy of 99mTechnetium-fluconazole nanocapsules. - Assis, Danielle Nogueira de (2008)
Several classes of antifungal have been employed in candidiasis treatment, but patients with advanced immunodeficiency can present unsatisfactory results after therapy. In these cases, high doses of drugs or the use of multiple agents are sometimes used, and hence increasing the risk of serious side effects. Considering theses difficulties, the encapsulation of antifungal agents in nanoparticulate carriers has been used with the objective of modifying the pharmacokinetic of drugs resulting in more efficient treatments with less side effects. The purpose of this work was the preparation, characterization and the investigation of the release profiles of radiolabeled fluconazole nanocapsules. The size, homogeneity and zeta potential of NC preparations were determined with a Zetasizer 3000HS. The morphology and the structural organization were evaluated by atomic force microscopy (AFM). The release study in vitro of NC was evaluated in physiologic solution with or without 70% mouse plasma. The labeling yield of fluconazole with 99mTc was 94% and the radiolabeled drug was stable within 24 h period. The encapsulation percentage of 99mTc-fluconazole in PLA-POLOX NC and PLA-PEG NC was approximately of 30%. The average diameter calculated by photon correlation spectroscopy (PCS) varied from 236 to 356 nm, while the average diameter determined by AFM varied from 238 to 411 nm. The diameter/height relation decreased significantly when 25% glutaraldehyde was used for NC fixation on mica. The zeta potential varied from −55 to −69 nm and surface-modified NC showed lower absolute values than conventional NC. The in vitro release of 99mTc-fluconazole in plasma medium of the conventional and surface-modified NC was greater than in saline. The drug release in plasma medium from conventional NC was faster than for surface-modified NC. The results obtained in this work suggest that the nanocapsules containing fluconazole could be used to identify infectious foci, due to the properties, such as size, zeta potential and controlled release of 99mTc-fluconazole. The surface-modified nanocapsules could constitute a long-circulating intravenous formulation of fluconazole for treating sepsis caused by disseminated form of candidiasis. However, in vivo studies should be considered and are under investigation.